2015
DOI: 10.1063/1.4905427
|View full text |Cite
|
Sign up to set email alerts
|

Gallium nitride nanowires and microwires with exceptional length grown by metal organic chemical vapor deposition via titanium film

Abstract: We present a new approach for synthesis of GaN nanowires and microwires by metal organic chemical vapor deposition via a thin titanium film evaporated onto sapphire substrate prior to growth. Titanium etches a two-dimensional GaN layer deposited at the initial stage and GaN nanowires subsequently emerge at the boundaries of the etched grains. These wires grow at an exceptional elongation rate of 18 μm/min and extend radially at a rate of 0.14 μm/min. The GaN layer between the wires grows at a rate of 0.1 μm/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…The self‐induced nucleation of GaN wires has been reported with molecular beam epitaxy (MBE) and hydride vapor phase epitaxy (HVPE) . Metal catalysts is currently used in GaN wires growth by metal–organic chemical vapor deposition (MOCVD) . The growth of self‐induced GaN wires by MOCVD has been reported using selective growth on patterned surfaces, which require a substrate preparation before the wire growth or a deposited layer …”
Section: Introductionmentioning
confidence: 99%
“…The self‐induced nucleation of GaN wires has been reported with molecular beam epitaxy (MBE) and hydride vapor phase epitaxy (HVPE) . Metal catalysts is currently used in GaN wires growth by metal–organic chemical vapor deposition (MOCVD) . The growth of self‐induced GaN wires by MOCVD has been reported using selective growth on patterned surfaces, which require a substrate preparation before the wire growth or a deposited layer …”
Section: Introductionmentioning
confidence: 99%
“…Традиционные методы формирования ННК и НМК основаны на использовании металлических катализаторов [1,2], селективной эпитаксии [3,4] или самоорганизации за счет упругих напряжений [5,6]. В последнее время в нашей лаборатории развивается технология роста НМК GaN, индуцированных нанослоем титана [7,8]. Показано, что эта технология позволяет достичь рекордных скоростей роста (∼ 800 мкм/ч) при сохранении высокого качества материала и выращивать структуры с НМК GaN длиной в сотни микрометров при малой продолжительности эпитаксиального процесса.…”
Section: Introductionunclassified
“…2 achieved nanowire arrays via VLS at 780 C. Tian et al 36 prepared micro-pyramids via SAG at a high temperature about 1080 C. Bae et al 37 investigated the morphologies of micro-pyramids, and they found that micropyramids with smooth sidewalls can only be grown at the temperature higher than 900 C. Rozhavskaya et al 3 reported the growth of micro-rod arrays under 1040 C. Thus, growth temperature of these micro-structures prepared via SAG (950-1175 C) [7][8][9][16][17][18]22,23 is much higher than that of nanowires prepared via VLS (760-850 C). 1,2,12,13,[24][25][26][27]29 Thus, it is still a challenge to simultaneous growth of all these nanostructures (including nanowires and micro-rods) under a favorable condition.…”
Section: 11mentioning
confidence: 99%
“…In comparison with the nanowire structure, [1][2][3][12][13][14][15]27,29 vertically aligned needle, rod and pyramid structures, which have a nanoscale tip and robust microscale-trunk, can bring advantages in single nano-structure devices [4][5][6] and optical coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation